Chemical Composition, Physical Properties, and the Oxidative Stability of Oil Bodies Extracted From Argania spinosa. (29th April 2018) - Zaaboul, Farah; Raza, Husnain; Lazraq, Abderrahim; Deng, Boxin; Cao, Chen; Liu, Yuan F.
Abstract: Oil bodies (OB) were extracted from argan kernels using an aqueous extraction method. The composition of OB revealed its lipid profile, which had a high content of stearic and palmitic acid. Besides, evidence suggested an association between OB and tocopherols. The physical properties of argan OB (AOB) showed that their size was around 1.9 μm and the ζ‐potential went from +17.7 mV at pH 2.0 to −32.25 mV at pH 8, with an isoelectric point around pH 5.1. OB were stable and small at pH 2.0, 7.0, and 8.0 but large near the pI. Additionally, AOB were stable against aggregation/coalescence even in high salt concentrations, and also against thermal processing (95 °C) with only a change in their interfacial properties. AOB emulsion showed interesting oxidative stability at different storage temperatures and heat treatment. Heat treatment and storage at low temperature preserved oleosins from degradation by the endogenous enzyme, and H‐oleosin 15 kDa resisted hydrolyzation even at a high storage temperature for 2 weeks.